Determinants of Adherence to Medical Therapy in Pregnant Patients with Systemic Lupus Erythematosus - Bushra,; Hussain, Muhammad Zahid; Bukhari, Syeda Kinza; Sheen, Irfan Najam; Khan , Muhammad Shahid; Hashmi , Zoha (Indus Journal of Bioscience Research, 2025)
Objective: To assess the determinants of adherence to medical therapy among pregnant patients with Systemic Lupus Erythematosus. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from August 2023 to February 2024 at CMH Multan. Methodology: A total of 196 pregnant women diagnosed with SLE were enrolled. Data were collected using a structured interview schedule and the 8-item Morisky Medication Adherence Scale (MMAS-8). Participants were assessed for socio-demographic factors, disease-related characteristics, and factors influencing adherence. Medication adherence was evaluated in relation to educational level, disease awareness, family support, and interaction with healthcare providers. Results: The mean age of participants was 29.05 ± 6.01 years, with a higher prevalence in rural areas (68.4%). Results showed that 91.3% of patients were confident in adhering to their medication regimen, but only 74% had satisfactory patient-provider communication. Conclusion: Key determinants such as education, disease awareness, communication with healthcare providers, and family support significantly affect medication adherence in pregnant women with SLE.